POLICY IMPLEMENTATION DALAM PEMELIHARAAN BERKALA JALAN POROS DESA:: Analisis Model Van Meter dan van Horn di Kabupaten Tuban - Arya Pratama Sagita Putri (Institut Pemerintahan Dalam Negeri, 2026)
Village trunk road infrastructure plays a crucial role in supporting regional connectivity and the local economy, particularly in the agricultural sector, which serves as the community’s mainstay. Although administrative data from the Tuban Regency Government indicates that the condition of village trunk roads reached 95.18% in 2024, on-the-ground observations reveal a paradox. Previous research on regional infrastructure implementation has tended to focus on the administrative evaluation of the physical construction of new roads, leaving a theoretical research gap regarding the dynamics of periodic maintenance that lacks an adaptive governance approach. The novelty of this study lies in its policy implementation analysis, which specifically highlights the gap between top-down bureaucratic administrative achievements and the ecological-participatory reality at the village level. This study aims to describe and analyze in depth the implementation process of the periodic maintenance program for village main roads by the Tuban Regency Public Works and Spatial Planning Agency (PUPR-PRKP). Using a descriptive qualitative method, data were collected through in-depth interviews, observations, and documentation, and then analyzed using the Van Meter and Van Horn model. The results indicate that administrative implementation proceeds smoothly, supported by high commitment from implementers; however, on the ground, it is hindered by weak communication, budget fluctuations, and technical standards that overlook local drainage issues. The policy implications of this study underscore the need for decentralized oversight involving community participation (Karang Taruna and village officials) as well as the integration of drainage development as a form of adaptive and sustainable infrastructure.